Development and Application of a Hydraulic Loading Test System That Provides Continuous and Stable Hydraulic Pressure - Jia-jun, Zeng; Zhi-Jun, Zhang; Cheng-zhi, Pu (Frontiers in Earth Science, 2020)
To accurately determine the stress characteristics of underground rock masses subjected to hydraulic pressure and reveal the crack-initiation, crack-propagation, and macromechanical characteristics of fractured rock masses under long-term hydraulic pressure, a hydraulic loading system that can deliver continuous and stable hydraulic pressure was developed. The system is composed of a device that supplies a stable hydraulic pressure, flowmeter, pressure gauge, acoustic emission instrument, loading device, and control system. The main innovation of the test system lies in the stabilization of the hydraulic pressure, which distinguishes the new system from traditional hydraulic loading devices and provides several advantages. First, in the new system, air pressure serves as the driving force, and water and gas coexist in the same cavity. Given the high compressibility of gas, the hydraulic pressure can still reach the relative stability during crack initiation and propagation in the specimen. Second, the device is capable of long-term operation with low energy consumption. In contrast to conventional hydraulic loading systems based on servo control, the hydraulic pressure of the new device can be maintained for a long time with little energy consumption. Finally, the device is simple to operate, low cost, convenient to assemble, and can be used in single-, double-, and triple-axis tests. The accuracy and reliability of the test system were verified through its application in the uniaxial compression test of a fractured body under the action of stable hydraulic pressure. The test system provides the foundation for the study of the physical mechanisms of deep underground rock masses subjected to long-term, stable seepage pressure.